Anatomy of a business plan : a step-by-step guide to building a business and securing your company's future - Pinson, Linda ([Place of publication not identifed] : Dearborn Trade Publishing, 2005)
It is the goal of this book to give you a clear, concise, and east-to-understand process to follow as you develop your business plan.
Business plan considerations -- The cover sheet and table of contents -- Executive summary -- Part I : The organizational plan -- Part II : The Marketing plan -- Plan III : Financial documents -- Supporting documents -- U.S. tax information -- Packaging your plan and keeping it up-to-date -- U.S. and international business research resources
Includes index.
Keywords: COMPLETE PLANNING